TOWARDS THE CAPITAL MARKET UNION - Iulian PANAIT (Hyperion Economic Journal, 2015)
This paper discusses the main characteristics of the proposed Capital Markets Union in Europe, as they are introduced by the European Commission and various authors, and emphasises some important advantages and disadvantages of this project for the developing and frontier markets in UE, especially for Romania.